1998
DOI: 10.1596/1813-9450-2027
|View full text |Cite
|
Sign up to set email alerts
|

Child Labor: Cause, Consequence, and Cure, with Remarks on International Labor Standards

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas abont development issues. An objective of tbe series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretationzs, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the view of the World Bank, its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
313
1
39

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 249 publications
(358 citation statements)
references
References 63 publications
5
313
1
39
Order By: Relevance
“…Footnotes 1 See Basu [1999] for an overview of the vast literature on child labor and labor standards.…”
Section: Comparative Staticsmentioning
confidence: 99%
“…Footnotes 1 See Basu [1999] for an overview of the vast literature on child labor and labor standards.…”
Section: Comparative Staticsmentioning
confidence: 99%
“…2 SeeFlora, Kraus, and Pfenning (1983) for Europe and US Bureau of the Census (1975) for the US. 3 SeeBasu (1999) and the references therein. All the empirical literature that investigate the phenomenon of child labor, either in the past of the nowadays developed economies or in contemporary developing economies, assumes that parents allocate the time of their children between child labor and schooling.…”
mentioning
confidence: 99%
“…Research often reveals negative effects of work in the labor market on school attendance and various indicators of attainment (Amin et al, 2006;Beegle et al, 2005;Psacharopoulos, 1997). However, some studies have found no relationship between such work and educational performance (Binder and Scrogin, 1998;Patrinos and Psacharopoulos, 1997) and some researchers have suggested that paid work may enable some children to attend school (Basu, 1999). Further complications are introduced by considerations of household work and gender.…”
Section: Research On Work By Children In Developing Areasmentioning
confidence: 99%